Effects of glaucoma surgery on visual field progression in open‐angle glaucoma considering the floor effect. Issue 5 (27th October 2021) - Schlatter, Andreas; Rauchegger, Teresa; Schmid, Eduard; Teuchner, Barbara
Abstract: Purpose: The aim of this retrospective analysis was to investigate whether trabeculectomy (TRAB) and XEN® Gel Stent implantation (XEN) – both filtrating surgery techniques – can slow down the deterioration of visual field (VF) parameters considering the floor effect, which could lead to a misestimation of pre‐ and postoperative VF rate of progression (ROP). Methods: Included in this study were patients with open‐angle glaucoma, who underwent either TRAB or XEN® gel stent implantation and who had at least three VF tests before and after surgery, over an observation period of 13 years. The annual ROP of the mean defect (MD) and the square root of loss variance (sLV) were calculated with two different censoring thresholds: by censored regression and by ordinary least squares regression (OLSR). In addition, the diagnostic range of sLV was calculated. Results: 48 eyes of 39 glaucoma patients were included in the study. The annual rate of MD progression was significantly reduced by filtering surgery when calculating the yearly ROP using OLSR (p = 0.006) and by censoring values exceeding a precalculated cut‐off of 14.20 dB (p = 0.041) and a cut‐off from the literature of 15.00 dB (p = 0.028). On average, the MD was impacted by a significant floor effect of 14.20 dB (95% CI: 12.83‐15.56), corresponding to 17.7/59 absolute defects or 29.9% of the whole VF. When applying both OLSR and censored regression, the annual rate of sLV progression did not show a significant difference. The sLV showed a diagnostic boundary at a MD of 15.78 dB. Conclusion: This study shows that filtering surgery can reduce the progression of VF in patients with open‐angle glaucoma, especially those whose disease develops aggressively. This is valid even if the floor effect in advanced cases is compensated by censored regression. On average, the ROP of MD is affected by a significant floor effect at about 29.9% absolute loss of the whole VF.